NEWS FROM ILAM: Digital Heritage Repatriation Workshop: 9-11 December 2008 (International Library of African Music, 2009)
The International Library of African Music (ILAM) held a very stimulating and productive workshop on "Producing, Preserving, and Repatriating Digital Cultural Heritage" on 9-11 December 2008 as the first outcome of its partnering relationship (est. July 2008) with the University of Michigan, Ann Arbor, African Studies Center (ASC). ASC Director Kelly Askew and ILAM Director Diane Thram, in cooperation with the University of Michigan's African Heritage Initiative (AHI), implemented the AHI plan to assist museums and universities in Ghana in their heritage preservation needs. This was done by organizing a workshop on the challenges, benefits, ethics and results of digitizing collections of cultural heritage materials, be they text, audio recordings, video/ film recordings, artefacts, or photographs.
Keywords: African Music